Photovoltaic packaging film
By adjusting the molecular weight, molecular weight distribution and long branched content of polyolefin elastomer, a photovoltaic packaging film with high light transmittance and high crosslinking degree was prepared, which solved the problem of long absorption time of POE film additives and low crosslinking degree. , improves production efficiency and reduces costs.
Patent Information
- Application Number
- CN202411778706.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-11
AI Technical Summary
During the preparation process, the additive absorption time of the existing POE film is relatively long and the crosslinking degree is relatively low, resulting in reduced production efficiency and increased cost.
By adjusting the molecular weight, molecular weight distribution and long branched content of the polyolefin elastomer, a photovoltaic encapsulation film with high light transmittance and high crosslinking degree was prepared to shorten the adsorption time of the additive.
The high light transmittance and high crosslinking degree of the photovoltaic packaging film are achieved, which shortens the adsorbing time, improves production efficiency and reduces costs.
Smart Images

Figure BDA0005172214720000111 
Figure BDA0005172214720000151
Abstract
Description
Technical Field
[0001] The invention relates to a photovoltaic component bonding material, in particular to a photovoltaic packaging film. Background Art
[0002] Solar power generation devices are a green and clean energy source. The most important core device is the solar photovoltaic cell module. The module is a sandwich device with a solar cell in the center, photovoltaic film on both sides of the cell, and photovoltaic glass or backplane on both sides of the film. The photovoltaic module is made by heating and laminating. The life and power generation performance of the photovoltaic module are restricted by other components of the module, and the most important part is the packaging film. The current mainstream packaging films include EVA, POE and EPE. Although EVA and EPE are relatively low in price, they have poor water vapor barrier properties, severe yellowing, and EPE has the risk of delamination. They are essentially not suitable as battery packaging materials.
[0003] There are basically no unsaturated bonds in the POE material structure, and it has excellent aging resistance, is non-polar, and has a low water vapor permeability, which is more conducive to protecting the battery cells. However, the preparation process of POE film requires POE particles to be mixed and absorbed with conventional film additives (such as peroxides / cross-linking agents / coupling agents, etc.), and then cast into film after all the conventional film additives are absorbed by POE. The main production problem currently exists is that the additive absorption time is long, resulting in reduced production efficiency of downstream customers, and under the same lamination conditions after casting into film, the cross-linking degree of POE film is low. In order to increase the cross-linking degree, it is usually necessary to increase the amount of film additives used, which leads to an increase in the cost of POE film. The above problems have become the main influencing factors restricting the development of downstream production of POE film. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a photovoltaic encapsulation film. The present invention can achieve high light transmittance and high crosslinking degree of the photovoltaic encapsulation film by adjusting the molecular weight, molecular weight distribution and long chain branch content of the main component polyolefin elastomer, and the auxiliary agent absorption time is shorter.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A photovoltaic encapsulation film comprises a polyolefin elastomer having the following characteristics:
[0007] a) molecular weight Mw = 45000-100000;
[0008] b) molecular weight distribution 2.1-2.7;
[0009] c) Long chain branch content I 10 / I2 is 15-30.
[0010] The inventors found in the continuous study of photovoltaic encapsulation film that when the molecular weight Mw of the polyolefin elastomer is 45000-100000 and the molecular weight distribution is 2.1-2.7, by further controlling the long chain branch content I 10 / I2 is 15-30, which can effectively improve the transmittance and cross-linking degree of the photovoltaic encapsulation film, and can also shorten the absorption time of the additive and improve production efficiency.
[0011] In some specific embodiments, the polyolefin elastomer also has at least one of the following characteristics:
[0012] d) Tg is -45°C to -65°C;
[0013] e) a melting point of 50-78°C;
[0014] f) Density: 0.85-0.878 g / cm 3 .
[0015] In some specific embodiments, the polyolefin elastomer is a copolymer of ethylene and α-olefin; the α-olefin is selected from one or more of propylene, butene, hexene, octene, nonene, and decene.
[0016] The technology for preparing polyolefin elastomers by copolymerization of ethylene and α-olefins is relatively mature in the art. The most typical application is the solution polymerization method, that is, a solution polymerization reaction is carried out in an organic solvent in the presence of a catalyst and a co-catalyst to obtain a polyolefin elastomer.
[0017] Among them, preliminary research has been conducted in this field on how to control the molecular weight and distribution of polyolefin elastomers and provide solutions, which provide a basis for the precise regulation of the microstructure of polyolefin segments and the customization of the performance of polyolefin materials. For example, "Liu Weifeng. Ethylene / octene solution copolymerization and regulation of polymer chain structure [D]. Zhejiang University [2024-12-05]" details the use of continuous solution copolymerization to prepare polymers with different molecular weights and distributions by adjusting the copolymerization activity of the catalyst, residence time, and molar ratio of different comonomers.
[0018] Regarding how to control the long-chain branch content of polyolefin elastomers, preliminary research has been conducted in this field and solutions have been provided. For example, patents CN116554370A and CN116162185B respectively proposed a metallocene catalyst with a new structure. They perform well in the high-temperature solution polyolefin process and can prepare polyolefins with ultra-high molecular weight. The resulting polymers have the characteristics of a high proportion of long-chain branches.
[0019] In order to simultaneously obtain a polyolefin elastomer whose characteristics such as molecular weight Mw, molecular weight distribution and long chain branch content meet the above-mentioned definitions, the present invention is preferably prepared by the following scheme, but it is only a feasible example of providing the polyolefin elastomer and does not serve as any limitation to the photovoltaic encapsulation film in the present invention.
[0020] The preparation method of the polyolefin elastomer is, for example:
[0021] In the presence of a catalyst (A+B) and a co-catalyst, ethylene and α-olefin are used as raw materials to carry out a solution polymerization reaction in an organic solvent to prepare a polyolefin elastomer.
[0022] Catalyst A (see patent CN111943973B) Catalyst B (see patent CN116554370A)
[0023] Wherein, the molar ratio of the catalyst A to the catalyst B is 1:(1-10).
[0024] The co-catalyst is at least one of alkyl aluminum, alkyl aluminum halide, alkyl aluminoxane, modified alkyl aluminoxane and optionally a boron salt, wherein the amount of the co-catalyst is calculated as the molar ratio of metal Al to the sum of metal Hf and metal Zr (expressed as M), and Al / M is 500-5000.
[0025] Preferably, the cocatalyst is selected from one or more of trimethylaluminum, triethylaluminum, tripropylaluminum, tributylaluminum, diethylaluminum monochloride, ethylaluminum dichloride, sesquiethylaluminum chloride, methylaluminumoxane, ethylaluminumoxane, propylaluminumoxane, triisobutylaluminum-modified methylaluminumoxane, triisobutylaluminum-modified ethylaluminumoxane, triisobutylaluminum-modified propylaluminumoxane, trioctylaluminum-modified methylaluminumoxane, and trioctylaluminum-modified ethylaluminumoxane;
[0026] Preferably, the boron salt is selected from one or more of tris(pentafluorophenyl)boron, tetrakis(pentafluorophenyl)boron, triphenylcarbon tetrakis(pentafluorophenyl)borate, NN dimethylaniline tetrakis(pentafluorophenyl)borate, and dioctadecyl(methyl)amine tetrakis(pentafluorophenyl)borate.
[0027] In the preparation method of the polyolefin elastomer provided by the present invention, the reaction is first carried out at a relatively low temperature and then the reaction temperature is increased. It is preferred to first control the reaction temperature to 130-145°C so that the polymer molecular weight increases rapidly to 20,000-40,000, and then the temperature is increased to 150-175°C until the target molecular weight reaches 45,000-100,000, at which time more long chain branches are generated. However, the molecular weight of the polyolefin elastomer should not be too high. Too high a molecular weight will increase the crystalline part, slow down the absorption of the additive and reduce the transmittance. Moreover, the molecular weight of the polyolefin elastomer should not be too low. Too low a molecular weight will make it difficult for the encapsulation film to form a body structure, affecting the crosslinking density and transmittance. At the same time, the long chain branch content of the polyolefin elastomer used in the present invention is 1 10 / I2 should not exceed 30. Too high long chain branches will significantly increase the steric hindrance, which will reduce the crosslinking degree. 10 / I2 should not be lower than 15. Too low long-chain branch content cannot be combined with the characteristics of molecular weight and its distribution to improve the crosslinking degree and transmittance.
[0028] In the above-mentioned method for preparing polyolefin elastomer, the reaction pressure is preferably 2-10 MPa, which is controlled by introducing raw material ethylene.
[0029] In addition, the above method can be used to prepare a polyolefin elastomer whose basic physical properties such as glass transition temperature, melting point, density, etc. meet the above requirements, and it can be applied to photovoltaic encapsulation film to have improved cross-linking, light transmittance, and additive absorption.
[0030] In some specific embodiments, the photovoltaic encapsulation film further comprises a cross-linking agent and optionally a co-cross-linking agent;
[0031] Preferably, the cross-linking agent is one or more of tert-butyl peroxy isopropyl carbonate, 2,5-dimethyl-2,5-(bis-tert-butylperoxy)hexane, tert-butyl peroxy carbonate-2-ethylhexyl ester, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-butyl peroxy 2-ethylhexyl carbonate, tert-amyl peroxy carbonate, tert-butyl peroxy 3,3,5-trimethylhexanoate;
[0032] Preferably, the amount of the cross-linking agent is 0.1-1.7% of the mass of the polyolefin elastomer.
[0033] In some specific embodiments, the auxiliary cross-linking agent is selected from multifunctional acrylates, preferably trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate, ditrimethylolpropane tetraacrylate, ditrimethylolpropane tetramethacrylate, propoxylated pentaerythritol tetraacrylate, tricyclohexane dimethanol diacrylate, propoxylated neopentyl glycol diacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, 2-butyl-2-ethyl-1,3-propanediol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, polyethylene glycol dimethacrylate;
[0034] Preferably, the amount of the auxiliary cross-linking agent is 0.4-3% of the mass of the polyolefin elastomer.
[0035] In some specific embodiments, the photovoltaic encapsulation film further comprises a silane coupling agent, preferably one or more of γ-chloropropylmethoxysilane, vinylethoxysilane, vinyltri(β-methoxyethoxy)silane, γ-methacryloxypropyltrimethoxysilane, vinyltriacetoxysilane, γ-glycidyloxypropyltrimethoxysilane, 3-(trimethoxysilyl)propyl-2-methyl-2-acrylate, anilinemethyltriethoxysilane, and octyltrimethoxysilane;
[0036] Preferably, the amount of the silane coupling agent is 0.1-1% by weight of the polyolefin elastomer.
[0037] Furthermore, the photovoltaic encapsulation film can be prepared by conventional methods in the art, for example, including the following steps: high-temperature premixing of raw materials, melt extrusion, film casting, cooling, slitting and winding processes. DETAILED DESCRIPTION
[0038] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.
[0039] Unless otherwise specified, the raw materials and reagents in the following examples of the present invention can be purchased through general commercial channels. Among them, catalyst A is provided by Examples 6-9 of patent CN111943973B; catalyst B is provided by Example 2 of patent CN116554370A.
[0040] The following instruments are used in the following embodiments of the present invention:
[0041] Melt index tester: ZwickMflow, test standard ASTM D1238
[0042] Single screw extruder (L / D=35), screw diameter 30mm
[0043] Molecular weight and molecular weight distribution tester: Polymer Char, GPC-IR
[0044] The test methods involved in the following embodiments of the present invention are:
[0045] 1. Long chain branch content of polyolefin elastomer: According to GB / T 3682.1 Plastics Thermoplastics Melt Mass Flow Rate (MFR) and Melt Volume Flow Rate (MVR) test methods, respectively test the melt index I under 10 kg weight at 190 ° C 10 The ratio of the melting index I2 at 190°C and 2.16 kg weight is I 10 / I2.
[0046] 2. Crosslinking degree of encapsulation film
[0047] The test method refers to the China Photovoltaic Industry Association standard T / CPIA 0006-2017 "Copolyolefin Film for Photovoltaic Module Encapsulation".
[0048] 3. Transmittance of packaging film
[0049] Take a piece of film with no pattern on the surface after lamination. Perform transmittance test according to the spectrophotometer method of GB / T 2410-2008, and calculate the average transmittance in the band range of 290nm-380nm and 380nm-1100nm respectively.
[0050] 4. The absorption time of the additives of the encapsulation film
[0051] See the quantitative evaluation method of auxiliary agent absorption time disclosed in patent CN118746677A.
[0052]
Preparation Example 1
[0053] 2.8 kg of octene was added to 4.2 kg of n-butane solvent to prepare a solution, which was then added to reactor a. The temperature was raised to 145°C, ethylene gas was introduced, and the pressure in the reactor was controlled to be 2.5 MPa. 1.1 mg of catalyst A and 5.2 mg of catalyst B were dissolved and added to reactor a together with 1.5 mol / L Al methylaluminoxane toluene solution. The amount of co-catalyst added was added according to a molar ratio of Al / M of 500, and the reaction was stirred for 8 minutes until the molecular weight of the polymer reached 25,000.
[0054] The reaction solution was then transferred to a reactor b at 160°C with an ethylene pressure of 2.5 MPa and the reaction was continued for 10 minutes to reach the target molecular weight. Water was added to the final reaction solution, cooled, filtered and dried to obtain an ethylene-octene copolymer, which was recorded as polyolefin elastomer A.
[0055]
Preparation Example 2
[0056] 3.08 kg of octene was added to 5.88 kg of Isopar E to prepare a solution, which was then added to reactor a. The temperature was raised to 135°C, ethylene gas was introduced, and the pressure in the reactor was controlled to be 3.5 MPa. 2 mg of catalyst A and 5.92 mg of catalyst B were dissolved and added to reactor a together with 1.5 mol / L Al methylaluminoxane toluene solution. The amount of co-catalyst added was added at a molar ratio of Al / M of 2000. The reaction was stirred for 7 minutes until the molecular weight of the polymer reached 28,000.
[0057] The reaction solution was then transferred to a reactor b at a temperature of 155°C and an ethylene pressure of 3.5 MPa, and the reaction was continued for 9 minutes to reach the target molecular weight. Water was added to the final reaction solution, cooled, filtered and dried to obtain an ethylene-octene copolymer, which was recorded as polyolefin elastomer B.
[0058]
Preparation Example 3
[0059] 1.9 kg of butene was added to 5.7 kg of Isopar E to prepare a solution, which was then added to reactor a. The temperature was raised to 130°C, ethylene gas was introduced, and the pressure in the reactor was controlled to be 3 MPa. 1.92 mg of catalyst A and 6.23 mg of catalyst B were dissolved and added to reactor a together with 7 wt% Al modified methylaluminoxane Isopar E solution. The amount of co-catalyst added was added at a molar ratio of Al / M of 4000, and the reaction was stirred for 10 minutes until the molecular weight of the polymer reached 35,000.
[0060] The reaction solution was then transferred to a reactor b at 168°C with an ethylene pressure of 3MP, and the reaction was continued for 6 minutes to reach the target molecular weight. Water was added to the final reaction solution, cooled, filtered and dried to obtain an ethylene-butene copolymer, which was recorded as polyolefin elastomer C.
[0061]
Preparation Example 4
[0062] 3.3 kg of hexene was added to 8.9 kg of Isopar E to prepare a solution, which was then added to reactor a. The temperature was raised to 140°C, and ethylene gas was introduced to control the pressure in the reactor to be 2.8 MPa. 7.86 mg of catalyst A and 3.96 mg of catalyst B were dissolved and added to reactor a together with 1.5 mol / L Al methylaluminoxane toluene solution. The amount of cocatalyst added was added at a molar ratio of Al / M of 5000. The reaction was stirred for 9 minutes until the molecular weight of the polymer reached 40,000.
[0063] The reaction solution was then transferred to a reactor b at a temperature of 170°C and an ethylene pressure of 2.8 MPa, and the reaction was continued for 4 minutes to reach the target molecular weight. Water was added to the final reaction solution, cooled, filtered and dried to obtain an ethylene-hexene copolymer, which was recorded as polyolefin elastomer D.
[0064]
Preparation Example 5
[0065] 3.1 kg of octene was added to 5.2 kg of n-butane solvent to prepare a solution, which was then added to reactor a. The temperature was raised to 143°C, ethylene gas was introduced, and the pressure in the reactor was controlled to be 5 MPa. 1.2 mg of catalyst A and 5.7 mg of catalyst B were dissolved and added to reactor a together with 1.5 mol / L Al methylaluminoxane toluene solution. The amount of co-catalyst added was added according to a molar ratio of Al / M of 900, and the reaction was stirred for 8 minutes until the molecular weight of the polymer reached 36,000.
[0066] The reaction solution was then transferred to a reactor b at a temperature of 175°C and an ethylene pressure of 5 MP, and the reaction was continued for 10 minutes to reach the target molecular weight. Water was added to the final reaction solution, cooled, filtered and dried to obtain an ethylene-octene copolymer, which was recorded as polyolefin elastomer E.
[0067]
Preparation Example 6
[0068] 3.8 kg of hexene was added to 9.3 kg of Isopar E to prepare a solution, which was then added to reactor a. The temperature was raised to 135°C, ethylene gas was introduced, and the pressure in the reactor was controlled to be 4 MPa. 7.63 mg of catalyst A and 5.49 mg of catalyst B were dissolved and added to reactor a together with 1.5 mol / L Al methylaluminoxane toluene solution. The amount of co-catalyst added was added at a molar ratio of Al / M of 2500. The reaction was stirred for 9 minutes until the molecular weight of the polymer reached 20,000.
[0069] The reaction solution was then transferred to a reactor b at 170°C with an ethylene pressure of 4 MP, and the reaction was continued for 4 minutes to reach the target molecular weight. Water was added to the final reaction solution, cooled, filtered and dried to obtain an ethylene-hexene copolymer, which was recorded as polyolefin elastomer F.
[0070]
Comparative preparation example 1
[0071] 2.35 kg of octene was added to 4.68 kg of Isopar E to prepare a solution, which was then added to a reactor, heated to 145°C, ethylene gas was introduced, and the pressure in the reactor was controlled to be 3.5 MPa. 16.4 mg of catalyst A was dissolved and added to the reactor together with a 7 wt% Al modified methylaluminoxane Isopar E solution, and the amount of co-catalyst added was added according to a molar ratio of Al / M of 800, and the reaction was stirred for 15 minutes. Water was added to the obtained reaction solution, cooled, filtered, and dried to obtain an ethylene-octene copolymer, which was recorded as polyolefin elastomer G.
[0072]
Comparative preparation example 2
[0073] 3.44 kg of hexene was added to 7 kg of n-butane to prepare a solution, which was then added to a reactor, heated to 135°C, and ethylene gas was introduced to control the pressure in the reactor to be 4 MPa. 23.6 mg of catalyst B was dissolved and added to reactor a together with 1.5 mol / L Al methylaluminoxane toluene solution, and the amount of co-catalyst added was added according to a molar ratio of Al / M of 700, and the reaction was stirred for 15 minutes. Water was added to the final reaction solution, cooled, filtered and dried to obtain an ethylene-hexene copolymer, which was recorded as polyolefin elastomer H.
[0074] The indices of the polyolefin elastomers prepared in Preparation Examples 1-6 and Comparative Preparation Examples 1-2 are summarized in Table 1.
[0075] Table 1
[0076]
[0077] [Example 1]
[0078] Prepare the following raw materials according to weight:
[0079] Polyolefin elastomer A 100 parts,
[0080] 1.2 parts of tert-butyl peroxy 2-ethylhexyl carbonate,
[0081] Triallyl isocyanurate 0.6 parts,
[0082] 0.2 parts of 3-(methacryloyloxy)propyltrimethoxysilane
[0083] Heat the above raw materials to 50°C and mix them evenly; after the additive is completely absorbed, adjust the parameters of the twin-screw extruder, the temperature from the feed port to the die head is 80°C, 90°C, 90°C, 90°C, 95°C, 95°C, 95°C, the screw speed is 45rpm, the traction speed is 0.7rpm, and the winding is 1.3rpm. After extrusion, cast film, cooling, slitting and winding processes, a photovoltaic encapsulation film is obtained with a film thickness of 0.6mm.
[0084] [Example 2]
[0085] Prepare the following raw materials according to weight:
[0086] Polyolefin elastomer B 100 parts,
[0087] 0.8 parts of tert-amyl peroxy 2-ethylhexyl carbonate,
[0088] 1 part of trimethylolpropane propane triacrylate,
[0089] Vinylethoxysilane 0.1 parts.
[0090] Heat the above raw materials to 50°C and mix them evenly; after the additive is completely absorbed, adjust the parameters of the twin-screw extruder, the temperature from the feed port to the die head is 80°C, 90°C, 90°C, 90°C, 95°C, 95°C, 95°C, the screw speed is 45rpm, the traction speed is 0.7rpm, and the winding is 1.3rpm. After extrusion, cast film, cooling, slitting and winding processes, a photovoltaic encapsulation film is obtained with a film thickness of 0.6mm.
[0091] [Example 3]
[0092] Prepare the following raw materials according to weight:
[0093] Polyolefin elastomer C 100 parts,
[0094] 0.7 parts of tert-amyl peroxy 2-ethylhexyl carbonate,
[0095] 0.5 parts of triallyl isocyanurate, 1 part of triethylene glycol dimethacrylate,
[0096] γ-Glycidyloxypropyltrimethoxysilane 0.5 parts.
[0097] Heat the above raw materials to 50°C and mix them evenly; after the additive is completely absorbed, adjust the parameters of the twin-screw extruder, the temperature from the feed port to the die head is 80°C, 90°C, 90°C, 90°C, 95°C, 95°C, 95°C, the screw speed is 45rpm, the traction speed is 0.7rpm, and the winding is 1.3rpm. After extrusion, cast film, cooling, slitting and winding processes, a photovoltaic encapsulation film is obtained with a film thickness of 0.6mm.
[0098] [Example 4]
[0099] Prepare the following raw materials according to weight:
[0100] Polyolefin elastomer D 100 parts,
[0101] 0.9 parts of tert-butyl peroxy 2-ethylhexyl carbonate, 0.3 parts of 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane
[0102] 1 part of trimethylolpropane propoxide triacrylate
[0103] γ-Glycidyloxypropyltrimethoxysilane 0.2 parts.
[0104] Heat the above raw materials to 50°C and mix them evenly; after the additive is completely absorbed, adjust the parameters of the twin-screw extruder, the temperature from the feed port to the die head is 80°C, 90°C, 90°C, 90°C, 95°C, 95°C, 95°C, the screw speed is 45rpm, the traction speed is 0.7rpm, and the winding is 1.3rpm. After extrusion, cast film, cooling, slitting and winding processes, a photovoltaic encapsulation film is obtained with a film thickness of 0.6mm.
[0105] [Example 5]
[0106] Prepare the following raw materials according to weight:
[0107] Polyolefin elastomer E 100 parts,
[0108] 1.2 parts of tert-butyl peroxy 2-ethylhexyl carbonate, 0.3 parts of 2,2-bis(tert-butylperoxy)butane
[0109] 1 part of trimethylolpropane triacrylate
[0110] 0.2 parts of vinyltriacetoxysilane.
[0111] Heat the above raw materials to 50°C and mix them evenly; after the additive is completely absorbed, adjust the parameters of the twin-screw extruder, the temperature from the feed port to the die head is 80°C, 90°C, 90°C, 90°C, 95°C, 95°C, 95°C, the screw speed is 45rpm, the traction speed is 0.7rpm, and the winding is 1.3rpm. After extrusion, cast film, cooling, slitting and winding processes, a photovoltaic encapsulation film is obtained with a film thickness of 0.6mm.
[0112] [Example 6]
[0113] Prepare the following raw materials according to weight:
[0114] Polyolefin elastomer F 100 parts,
[0115] 0.5 parts of tert-butyl peroxy 2-ethylhexyl carbonate, 0.3 parts of tert-amyl peroxy 2-ethylhexyl carbonate
[0116] 0.4 parts of ethoxylated pentaerythritol tetraacrylate, 0.3 parts of triallyl isocyanurate and 0.2 parts of vinyl triacetoxysilane.
[0117] Heat the above raw materials to 50°C and mix them evenly; after the additive is completely absorbed, adjust the parameters of the twin-screw extruder, the temperature from the feed port to the die head is 80°C, 90°C, 90°C, 90°C, 95°C, 95°C, 95°C, the screw speed is 45rpm, the traction speed is 0.7rpm, and the winding is 1.3rpm. After extrusion, cast film, cooling, slitting and winding processes, a photovoltaic encapsulation film is obtained with a film thickness of 0.6mm.
[0118] [Comparative Example 1]
[0119] A photovoltaic encapsulation film was prepared according to the same formula and method as in Example 1, except that polyolefin elastomer A was replaced by polyolefin elastomer G.
[0120] [Comparative Example 2]
[0121] A photovoltaic encapsulation film was prepared according to the same formula and method as in Example 4, except that the polyolefin elastomer D was replaced by polyolefin elastomer H.
[0122] The photovoltaic encapsulation films prepared in the embodiments and comparative examples were subjected to the performance tests shown in Table 2, and the results are as follows.
[0123] Table 2
[0124]
[0125] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A photovoltaic encapsulation film, characterized in that: Includes polyolefin elastomers having the following characteristics: a) molecular weight Mw = 45000-100000; b) molecular weight distribution 2.1-2.7; c) Long chain branch content I 10 / I2 is 15-30.
2. The photovoltaic encapsulation film according to claim 1, characterized in that: The polyolefin elastomer also has at least one of the following characteristics: d) Tg is -45°C to -65°C; e) a melting point of 50-78°C; f) Density: 0.85-0.878 g / cm 3 .
3. The photovoltaic encapsulation film according to claim 1, characterized in that: The polyolefin elastomer is a copolymer of ethylene and α-olefin; the α-olefin is selected from one or more of propylene, butene, hexene, octene, nonene and decene.
4. The photovoltaic encapsulation film according to any one of claims 1 to 3, characterized in that: The photovoltaic encapsulation film further comprises a cross-linking agent and optionally a co-cross-linking agent; Preferably, the cross-linking agent is one or more of tert-butyl peroxy isopropyl carbonate, 2,5-dimethyl-2,5-(bis-tert-butylperoxy)hexane, tert-butyl peroxy carbonate-2-ethylhexyl ester, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-butyl peroxy 2-ethylhexyl carbonate, tert-amyl peroxy carbonate, tert-butyl peroxy 3,3,5-trimethylhexanoate; Preferably, the amount of the cross-linking agent is 0.1-1.7% of the mass of the polyolefin elastomer.
5. The photovoltaic encapsulation film according to claim 4, characterized in that: The auxiliary cross-linking agent is selected from multifunctional acrylates, preferably trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate, ditrimethylolpropane tetraacrylate, ditrimethylolpropane tetramethacrylate, propoxylated pentaerythritol tetraacrylate, tricyclohexane dimethanol diacrylate, propoxylated neopentyl glycol diacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, 2-butyl-2-ethyl-1,3-propanediol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, polyethylene glycol dimethacrylate; Preferably, the amount of the auxiliary cross-linking agent is 0.4-8% of the mass of the polyolefin elastomer.
6. The photovoltaic encapsulation film according to any one of claims 1 to 5, characterized in that: The photovoltaic encapsulation film further comprises a silane coupling agent, preferably one or more of γ-chloropropylmethoxysilane, vinylethoxysilane, vinyltri(β-methoxyethoxy)silane, γ-methacryloxypropyltrimethoxysilane, vinyltriacetoxysilane, γ-glycidyloxypropyltrimethoxysilane, 3-(trimethoxysilyl)propyl-2-methyl-2-acrylate, anilinemethyltriethoxysilane, and octyltrimethoxysilane; Preferably, the amount of the silane coupling agent is 0.1-2% of the mass of the polyolefin elastomer.
Citation Information
Patent Citations
A metallocene catalyst and preparation method and its application in olefin polymerization
CN116162185B
Metallocene catalyst and preparation method and application thereof
CN116554370A
Polyolefin elastomer and application thereof in photovoltaic packaging film
CN116789883A
Photovoltaic adhesive film with low water vapor transmittance as well as preparation method and application of photovoltaic adhesive film
CN117417712A
Highly branched polyethylene as well as preparation method and application thereof
CN117886983A
Cited By
Polyolefin elastomer for photovoltaic packaging film, preparation method and application
CN121362278A
A polyolefin elastomer for photovoltaic encapsulation films, its preparation method and application
CN121362278B